COMPARATIVE ANALYSIS OF MORPHOLOGICAL STRUCTURES IN INDO-EUROPEAN LANGUAGES - Gulmira Usmonova; Madina Abjaparova; Ruxshona Valiyeva (TADQIQOTLAR, 2025)
Abstract This study presents a comparative analysis of morphological structures within selected Indo-European languages, focusing on the typological diversity and historical development of inflectional and derivational morphology. The Indo-European language family, which includes English, Sanskrit, Greek, Latin, Russian, and others, demonstrates both shared grammatical roots and unique evolutionary paths. By analyzing morphological features such as case marking, verb conjugation, and nominal declension, this research identifies patterns of retention, innovation, and simplification across branches. Special attention is given to how morphological systems reflect broader syntactic and phonological changes over time. The study employs a comparative-historical method, drawing on linguistic data from classical and modern sources to examine both fusional and analytical tendencies within the family. Results show that morphological complexity correlates with historical linguistic change and language contact, influencing how modern Indo-European languages express grammatical relations. This analysis contributes to understanding the evolution of morphological typology and the mechanisms of linguistic diversification.